The role of the acute phase protein PTX3 in the ventilator-induced lung injury - JM Real (European Respiratory Review, 2008)
The pentraxin 3 (PTX3) is an acute phase proinflammatory protein produced by fibroblasts and alveolar epithelial cells. We have previously demonstrated that PTX3 is a key modulator of inflammation. Mechanical ventilation (MV) is a life saving therapeutic approach for patients with acute lung injury that, nevertheless could lead to an inflammatory response and tissue injury (ventilator-induced lung injury: VILI), representing a major cause of iatrogenic lung damage in intensive units. Our objective was to investigate the role of PTX3 in VILI. PTX3 transgenic, knockout and Wt control mice (n = 12/group) were ventilated (45ml·kg–1) until respiratory system Elastance increased 50% (Ers150%), an indicator of VILI. Histological analysis demonstrated that using a Ers150% was appropriate for our analysis since identical degrees of inflammation were observed in Tg, KO and Wt mice as assessed by leukocyte infiltration, oedema, alveolar collapse and number of breaks in alveolar septa. However, Tg mice reached Ers150% faster than Wt controls (p = 0.0225). We also showed that the lack of PTX3 does not abolish the occurrence of VILI in KOs. Gene expression profile of PTX3, IL-1beta, IL-6, KC, IFNgamma, TGFbeta and PCIII were investigated by QPCR. MV drastically up modulated PTX3 as well as IL-1beta, IL-6, IFNgamma and KC. Alternatively, mice were ventilated for 20, 40 and 60 min. The faster kinetics of Tg mice to reach Ers150% was accompanied by an earlier augmentation of IL-1b and PTX3 expression. The kinetics of local PTX3 expression in the lungs of ventilated mice strongly suggests the involvement of this pentraxin in the pathogenesis of VILI.